PENGARUH PENGAWASAN TERHADAP SEMANGAT KERJA PEGAWAI PADA KANTOR DINAS PENDIDIKAN KABUPATEN KUTAI TIMUR - Supardi . (ADMINISTRASI PUBLIK, 2018)
The purpose of this study is to determine whether supervision has an effect on employee morale of the Office of Education of East Kutai Regency. To get the data the authors do research on The results showed that the supervision effect on employee morale of Education Office of East Kutai Regency. It can be proven that the results of data analysis rs count obtained greater than the table value that is 0.770> 0.456 at the level of confidence 95 % for N = 14.             Thus the hypothesis of this study can be accepted that the supervision effect on employee morale at the Office of Education of East Kutai Regency.